Molecular Detection of New Delhi Metallo Beta Lactamase 1 (NDM-1) - Producing Salmonella Typhi in Patients with Typhoid Fever - Qasim S. Al-Mayah (Journal of Global Pharma Technology, 2020)
Background: Antibiotic resistance among different pathogenic bacteria becomes a major therapeutic change and requires prompt solutions. Aims: this study aimed to investigate the prevalence of New Delhi metallo-β-lactamase-1 (blaNDM-1) gene in Salmonella Typhi isolated from patients with typhoid fever. Materials and Methods: This a cross-sectional study including 100 patients with typhoid fevers. A blood sample was collected from each patient, and cultivated on a selective media for Salmonella where the diagnosis was made phenotypically and by API20E system. Disk diffusion test was used to examine the microbial sensitivity to imipenem and meropenem, while the ability of the bacteria to produce the carbapenemase was examined using Modified Hodge’s test. For blaNDM-1gene detection, the plasmid DNA was extracted and a specific set of primers was used to amplify this gene in conventional polymerase chain reaction (PCR). Results: Out of 100 patients, 37 (37%) had a positive blood culture, of which 13 isolates showed some antibiotic resistance: 7 isolates for imipenem, 4 isolates to meropenem, and 2 isolates both antibiotics. Of those 13 isolates, 10 (76.9 %) were positively showing their ability to produce carbapenemases, while 9 isolates (69.2%) showed a successful blaNDM-1 gene amplification. Conclusions: There is a relatively high rate of carbapenemases-producing and as well as NDM-1 producing S. Typhi strains among Iraqi patients with typhoid fever